Natural mortality of cod (Gadus morhua) in the Southern Gulf of St Lawrence - Sinclair, A. F. (ICES Journal of Marine Science, 2001)
The closure of the cod fishery in Canada's southern Gulf of St Lawrence, and the existence of a reliable research vessel (RV) survey of the stock, has provided a unique opportunity to directly estimate the instantaneous rate of natural mortality (M) of a commercial cod stock. The results indicate that M is currently in the range of 0.4, which is higher than the value of 0.2 assumed in the past. An M of 0.4 is not inconsistent with the observed age range of cod in commercial catches and with recent growth characteristics of the stock. There is evidence that M may have increased in the early 1980s.